Unraveling the interplay: Exploring the relationship between children's obesity, sleep disorders, depressive symptoms, and age dynamics - Betül Orhan Kiliç; Eda Çakmak (National Scientific Medical Center, 2023)
Objective: This study explores the relationships between sleep disorders, depressive symptoms, and obesity among children of different ages. Material and methods: The data for this study were collected from 163 Turkish children aged 7 to 10 and 11 to 15 years (mean age=9.4, SD=1.9) who were attending well-child visits. Parents completed an online questionnaire on sociodemographic data, while children completed the Children Depression Inventory and The Children's Sleep Habits Questionnaire. Results: The regression model for the 7-10 years group included sleep resistance, sleep onset delay, nighttime awakenings, and daytime sleepiness, and explained 33.8% of the variance in Children Depression Inventory scores (R2=0.338, F=9.779, p<0.001). For the 11-15 age group, the regression model included obesity status, Children's Sleep Habits Questionnaire scores, sleep onset delay, sleep-related anxiety, and sleep-disordered breathing, and explained 80.3% of the variance in Children Depression Inventory scores (R2=0.803, F=28.489, p<0.001). Conclusion: Overall, the results of this study emphasize the significance of addressing sleep disorders, obesity, and depressive symptoms in children, particularly in adolescents, to promote better mental health outcomes.